Mesenchymal Stromal Cells’ Therapy for Polyglutamine Disorders: Where Do We Stand and Where Should We Go? - Barros, Inês; Marcelo, Adriana; Silva, Teresa P.; Barata, João; Rufino-Ramos, David; Pereira de Almeida, Luís; Miranda, Catarina O. (Frontiers in Cellular Neuroscience, 2020)
Polyglutamine (polyQ) diseases are a group of inherited neurodegenerative disorders caused by expansion of the cytosine-adenine-guanine (CAG) repeat. This mutation encodes an extended glutamine (Q) tract in the disease protein, resulting in the alteration of its conformation/physiological role and in the formation of toxic fragments/aggregates of the protein. This group of heterogeneous disorders share common molecular mechanisms, which opens the possibility to develop a pan therapeutic approach. Vast efforts have been made to develop strategies to alleviate disease symptoms. Nonetheless, there is still no therapy that can cure or effectively delay disease progression of any of these disorders. Mesenchymal stromal cells (MSC) are promising tools for the treatment of PolyQ disorders, promoting protection, tissue regeneration and/or modulation of the immune system in animal models. Accordingly, data collected from clinical trials have so far demonstrated that transplantation of MSC is safe and delays the progression of some PolyQ disorders for a period of time. However, to achieve sustained phenotypic ameliorations in clinics, several treatments may be necessary. Therefore, efforts to develop new strategies to improve MSC’s therapeutic outcomes have been emerging. In this review we discuss the current treatments and strategies used to reduce PolyQ symptoms and major pre-clinical and clinical achievements obtained with MSC transplantation as well as remaining flaws that still have to be overcome. The need to cross the blood-brain-barrier, together with a short rate of cell engraftment in the lesioned area and low survival of MSC in pathophysiological context upon transplantation may contribute to the transient therapeutic effects. We also review methods like pre-conditioning or genetic engineering of MSC that can be used to increase MSC survival in vivo, cellular-free approaches – i.e., MSC-conditioned medium (CM) or MSC-derived extracellular vesicles (EVs) as a way of possibly replacing the use of MSC and methods required to standardize the potential of MSC/MSC-derived products. These are fundamental questions that need to be addressed as to obtain maximum MSC performance in PolyQ diseases and therefore increase clinical benefits.